Los cuentos tridimensionales como estrategia en el desarrollo de la inteligencia emocional en niños de 4 a 5 años de edad, del ‘‘Centro de Educación Inicial Teresa León de Noboa’’ en la provincia de Bolívar, cantón Guaranda, Periodo 2025. - Tisalema Pilamunga, Shirley Tatiana (2025)
Dear reader, in the following pages of this research, you will find a detailed approach regarding three-dimensional stories and their contribution to the development of emotional intelligence in children aged 4 to 5 years who attend the "Centro de Educación Inicial Teresa León de Noboa" in person, located in Guaranda, Province of Bolívar. It start from the lack of understanding about the emotions they exhibit at this stage, which can negatively affect their academic performance, interpersonal relationships, and especially their individual well-being. In order to address this issue, three-dimensional stories are used as an innovative alternative, integrating visual, tactile, and narrative materials that will generate meaningful and emotional educational experiences. Developed under a qualitative approach using primarily a direct observation sheet applied to 25 children in the classroom, and an interview with the teacher in charge, resulting in the finding that the strategy employed positively benefits the children, helping them make significant progress in their empathy, self-regulation, and emotional expression. It is also identified that the students are able to share personal experiences based on the stories. Finally, a proposal was designed based on 10 different activities related to the proposed theme, aiming to enhance early emotional skills both inside and outside the classroom. Additionally, the incorporation of these stories as a permanent part of the emotional reading corner is suggested, promoting the independent use by children.